Efectos de la crisis sanitaria causada por covid-19 y su impacto en el comercio exterior del Ecuador durante el 2020. - Jaramillo Orellana, Erika Luisiana (My University, 2021)
The global health crisis resulting from the COVID-19 pandemic declared on March 11, 2020, has represented a great challenge for all developed and developing countries, including Ecuador, since health systems were put to the test, it also delves into economic and social problems. In 2020, the Gross Domestic Product of Ecuador decreased due to a significant fiscal deficit and stagnation of economic growth, this product of the confinement and impact of international trade activities. Through this investigation, the main objective of determining the effects of the health crisis caused by COVID-19 on the development of Ecuador's foreign trade activities was met. A quantitative research was used in which two or more variables are related in the statistical analysis, and correlational where the statistics are measured in relation to the effects of COVID-19 in international trade activities. Quantitative research refers to the use of computer, statistical and mathematical tools to obtain results, that is, through this research the problem is quantified. In correlational research, it is used to measure two variables through the exploration of information. Therefore, it is important to emphasize the influence that foreign trade has on the Ecuadorian economy, the effect of the suspension of productive activities and the international uncertainty of Ecuador's main trading partners have been determining factors in the magnitude of the impact. in the trade balance and in the Gross Domestic Product (GDP) of the country. The contraction in the volume of Ecuadorian foreign trade was caused since March 2020 when China temporarily closes its borders, which causes the suspension of exports of inputs forcing the paralysis of activities of its main suppliers in the American continent. The COVID-19 pandemic negatively affected the Ecuadorian economy since exports of goods and services decreased significantly, however, it is highlighted that, despite the impact of the pandemic in the international context, some Ecuadorian products had a positive performance in their sales. The Ministry of Production, Foreign Trade, Investment and Fisheries (2020) of Ecuador determined that, in the first weeks of the health emergency, the sales of the entire economic sector were reduced by 42%, which is equivalent to a loss of 1,505 million dollars for Ecuadorian businesses and households. Companies engaged in agricultural, livestock, forestry, fishing and mining production activities had lower losses because they were excluded from mobility restrictions. The shrimp aquaculture and fishing sector registered a positive variation rate with respect to the performance in the second half of 2019 as the international demand for this product increased significantly. It should be noted that Ecuadorian companies were obliged to boost their activities to maintain a competitive level against companies from other countries, including developing electronic programs that allow them to manage their production and trade activities through internet tools (networks social, web pages among others). In conclusion, it is determined that foreign trade activities were affected by the significant drop in prices of the main traditional and non-traditional products such as oil, shrimp, bananas, cocoa, coffee, tuna and other tropical fruits, as a result of confinement measures due to the presence of COVID-19. However, the internal economic situation of Ecuadorian companies has been progressively improving with encouraging economic indicators that show the improvement of the economy through the gradual reactivation of the productive apparatus, reflected in the level of sales to international.
La crisis sanitaria mundial producto de la pandemia del COVID-19 declarada el 11 de marzo del 2020, ha representado un gran reto para todos los países desarrollados y en vías de desarrollo entre ellos Ecuador, ya que se puso a prueba los sistemas de salud, sino que también profundiza en los problemas económicos y sociales. En el año 2020, el Producto Interno Bruto del Ecuador se redujo debido a un importante déficit fiscal y estancamiento del crecimiento económico esto producto del confinamiento y afectación de las actividades de comercio internacional. A través de la presente investigación se cumplió con el principal objetivo de determinar los efectos que la crisis sanitaria causada por el COVID-19 en el desarrollo de las actividades de comercio exterior del Ecuador. Se utilizó una investigación de tipo cuantitativo en la cual se relacionan dos o más variables en el análisis de estadísticas, y, correlacional donde se mide las estadísticas con relación a los efectos del COVID-19 en las actividades de comercio internacional. La investigación cuantitativa hace referencia al uso de herramientas informáticas, estadísticas y matemáticas para obtener resultados, es decir a través de esta investigación se cuantifica el problema. En la investigación correlacional se utiliza para medir dos variables a través de la exploración de información. Por lo tanto, es importante hacer énfasis en la influencia que tiene el comercio exterior en la economía ecuatoriana, el efecto de la suspensión de las actividades productivas y la incertidumbre internacional de los principales socios comerciales del Ecuador han sido factores determinantes en la magnitud de afectación en la balanza comercial y en el Producto Interno Bruto (PIB) del país. La contracción del volumen del comercio exterior ecuatoriano fue causada desde marzo del año 2020 cuando China cerró temporalmente sus fronteras lo cual provocó la suspensión de exportaciones de insumos Y OTROS PRODUCTOS (semi procesados-procesados) obligando a la paralización de actividades de sus principales proveedores del continente americano. La pandemia del COVID-19 afectó negativamente a la economía ecuatoriana ya que las exportaciones de bienes y servicios disminuyeron significativamente, sin embargo, se destaca que, pese al impacto de la pandemia en el contexto internacional, algunos productos ecuatorianos tuvieron un desempeño positivo en sus ventas. El Ministerio de Producción, Comercio Exterior, Inversiones y Pesca (2020) del Ecuador determinó que, en las primeras semanas de la emergencia sanitaria, las ventas de todo el sector económico se redujeron en un 42% que equivale a una pérdida de 1.505 millones de dólares para las empresas y hogares ecuatorianos. Las empresas dedicadas a las actividades de producción de agricultura, ganadería, silvicultura, pesca y explotación de minas tuvieron menores pérdidas debido a que fueron excluidas de las restricciones de movilidad. El sector de acuicultura y pesca de camarón registró una tasa de variación positiva con respecto al desempeño en el segundo semestre del 2019 ya que aumentó significativamente la demanda internacional de este producto. Cabe destacar que las empresas ecuatorianas se vieron en la obligación de dinamizar sus actividades para mantener un nivel competitivo frente a empresas de otros países entre eso, desarrollar programas electrónicos que les permitan manejar sus actividades de producción y comercio a través de herramientas de internet (redes sociales, páginas web entre otras). En conclusión, se determina, que en las actividades de comercio exterior se vieron afectadas por la caída significativa de precios de los principales productos tradicionales y no tradicionales como son petróleo, camarón, banano, cacao, café, atún y otras frutas tropicales, resultado de las medidas de confinamiento por presencia del COVID-19. Sin embargo, la situación económica interna de las empresas ecuatorianas ha ido mejorando progresivamente con indicadores alentadores de coyuntura que muestran la mejoría de la economía a través de la reactivación paulatina del aparato productivo, reflejado en el nivel de ventas hacia los mercados internacionales.
Keywords: FOREIGN TRADE